Mutual assistance, collaborative communication, and teacher work responsibility: a mediation analysis - Ahmad Sabandi; Tia Ningrum (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study examines whether mutual assistance behavior influences teacher work responsibility directly and indirectly through collaborative communication as a mediating variable. Using a quantitative cross-sectional design, data were collected from 482 public high school teachers in West Sumatra Province, Indonesia, selected via proportional stratified random sampling. Instruments were validated through expert review (content validity) and pilot testing (AVE > 0.50; Composite Reliability > 0.70). Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results indicate that mutual assistance significantly and positively affects collaborative communication (β = 0.719, T = 22.884, p < 0.001) and work responsibility (β = 0.434, T = 12.124, p < 0.001), and that collaborative communication significantly predicts work responsibility (β = 0.603, T = 18.536, p < 0.001), confirming a mediation pathway. These findings indicate that teacher responsibility is shaped not only by individual attributes but also by the quality of collaborative social interactions. School management strategies that systematically cultivate mutual assistance and strengthen communication-based collaboration are recommended to build sustainable professional responsibility.